Reims/Durocortorum, cité des Rèmes : les principales étapes de la formation urbaine - Robert Neiss; François Berthelot; Jean-Marc Doyen; Philippe Rollet (Gallia)
For a long time, Reims’ history only began with Caesar and the Gallic Wars. Despite an ancient mythology claiming an origin as ancient as Rome’s, previous archaeological pieces of evidence weren’t reliable and were mainly ignored. Preventive archaeology gradually gathered data attesting to a settlement founded at least around the 2nd c. BC. The inventory of old finds even allows us to speculate on an earlier origin and to make out an evolution through large successive stages, resulting in the Augustan city and showing themselves in tangible changes in the city shape. Documents dating back to La Tene match the birth of Reims site to the organization of Remi’s territory. A vast space of an unknown function developed very early under the aegis of a sanctuary overlooking the site. Then, in the 2nd c. BC, settlements multiplied in the centre of the basin shaping the siting of the future town. Shortly before the Conquest, an oppidum precisely delineated the settlement’s boundaries, and the latter quickly grew later on. Then, the rise of the town to the position of provincial capital coincided with an ambitious new founding initiative which created an urban area of 500 ha, surrounded by a gigantic city wall of which the layout seems to recall the ancient founding of the site and shows a remarkable continuity in the land settling and in the general plan.